How education and GDP drive the COVID-19 vaccination campaign - Vu M. Ngo; Klaus F. Zimmermann; Phuc V. Nguyen; Toan L.D. Huynh; Huan H. Nguyen (Global Labor Organization (GLO), 2021)
Since vaccination is the decisive factor for controlling the COVID-19 pandemic, it is important to understand the process to vaccination success. We identify a variety of factors playing a crucial role including the availability of vaccines, pandemic pressures, economic strength (GDP), educational development and political regimes. Examining the speed of vaccinations across countries, we find that initially authoritarian countries are slow in the vaccination process, while education is most relevant for scaling up the campaign and financial strength of the economies drive them to higher vaccination rates.
Keywords: D72; C30; P16; I19; 330; COVID-19; educational development; political regimes; vaccination